The Iron Status of Parturient Mothers and their New Born Babies - Goonawardene, I.M.R.; Liyanage, C. (My University, 1996)
To evaluate the iron status of women in labour. To evaluate the iron status in :he neonates of these subjects. To study the correlation between the iron status of these subjects and in their new born babies